Methane emission characteristics and model of CBM wells - Dong, Qingxiang; Wang, Shengwei; Ma, Jinkui; Lyu, Shuaifeng; Lu, Weiyong (Frontiers in Earth Science, 2023)
CBM (CBM) development in coal mining area has good safety, economic and energy benefits, but methane emission is common in surface well sites. In view of this, taking the CBM wells in Qinshui County of Shanxi Province as an example, the methane emission location and emission volume of CBM wells are obtained, and the prediction model of methane emission volume is established through field investigation and multiple regression analysis. The results show that 81% of CBM wells have methane emission. Wellhead and drainage outlet are the two main positions of methane emission. The proportion of wells with emission volume between 0 and 10 m3/d is 59%. On the whole, the emission accounts for 1.53% of the gas well production. There is almost no methane emission in the single liquid phase flow stage. The methane emission in the gas-liquid two-phase flow stage is positively correlated with the bottom hole flow pressure, times of stroke and gas production, and negatively correlated with the pump embedment and water production. The bottom hole flow pressure and the pump embedment have the greatest impact on the methane emission. In the single-phase gas flow stage, methane emission is positively correlated with gas production and casing pressure, and negatively correlated with stroke frequency and water production.